Flowers in the garden: a glance on multilingualism in Malaysia - Abdullah, Ain Nadzimah; Talif, Rosli; Mohd Jan, Jariah (Malaysian Association of Modern Languages, 2012)
This paper examines the recent changes to the Malaysian linguistic situation that had grave implications for the modifying of the language use in education. It discusses the status of English in pre- and early independent years and how language was revolutionised and replaced due to the widespread communicative use of Bahasa Melayu. Issues that underlie teacher apprehension as a result of the policy change and their language preferences are also highlighted. Investigating and understanding their apprehensions will help policy makers understand the impinging forces that have an impact on any policy innovation.